Photosensitization of peptides and proteins by pterin derivatives - Dántola, María Laura (2017)
Proteins are one of the preferential targets of the photosensitized damaging effects of ultraviolet (UV) radiation on biological system. Pterins belong to a family of heterocyclic compounds, which are widespread in living systems and participate in relevant biological functions. In pathological conditions, such as vitiligo, oxidized pterins accumulate in the white skin patches of patients suffering this depigmentation disorder. It is known that pterins are able to photosensitize damage in nucleotides and DNA by type I (electron transfer) and type II (singlet oxygen) mechanisms. Recently, it has been demonstrated that proteins and its components may also be damaged when solutions containing both proteins and pterin are exposed to UV-A radiation. Therefore, given the biological and medical relevance of the photosensitizing properties of these molecules, we present in this article an overview of the capability of different pterin derivatives to photoinduce damage in proteins present in the skin, focusing our attention on the chemical modifications of tyrosine and tryptophan residues.